pengembangan media pembelajaran berbasis augmented reality (AR) pada pembelajaran IPAS topik Panca Indra kelas IV (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to determine the validity, practicality, and effectiveness of Augmented Reality (AR)-based learning media in teaching the “Five Senses” topic in the Natural Sciences curriculum for fourth-grade students at SDN 107400 Bandar Khalipah. This study was designed as a research and development (R&D) project using the ADDIE model, which consists of five stages: analyze, design, development, implementation, and evaluation. The data collection techniques used included questionnaires, tests, documentation, and interviews. The subjects of this study were the fourth-grade students at SDN 107400 Bandar Khalipah, totaling 20 students. The research results showed that 82% of the questionnaire validation results fell into the “highly acceptable” category, 84.61% of the material validation test results fell into the “highly acceptable” category, 85% of the test validation results fell into the “highly acceptable” category, 93% of the media validation results fell into the “highly acceptable” category, and the practicality test yielded a score of 90%, falling into the “highly acceptable” category. The effectiveness of the instructional media was determined based on pre-test and post-test scores using the N-Gain percentage formula, yielding a result of 70.13%, which falls into the “moderately effective” category. Based on these data, it can be concluded that this research and development effort has produced a viable, practical, and effective product for use in the learning process.